Моделювання бактеріального хемотаксису в середовищі з репелентом - Vasilev, O. M.; Karpenko, V. O. (Publishing house "Academperiodika", 2018)
The bacterial chemotaxis in a one-dimensional system with a repellent has been considered. The process of bacterial redistribution in the system is analyzed, and a corresponding phenomenological model is proposed, which makes allowance for the diffusion of bacteria and their motion caused by the repellent gradient. The repellent injection into the system is governed by boundary conditions. In the framework of this model, the chemotaxis sensitivity function, a numerical characteristic, which describes the nonuniformity in the bacterial distribution, is calculated. A dependence of the chemotaxis sensitivity function on the repellent concentration at the system boundaries is obtained. A relation between the bacterial distribution and the parameters of repellent distribution is found.